Characterization of a Merkel Cell Polyomavirus-Positive Merkel Cell Carcinoma Cell Line CVG-1 - Velásquez, Celestino; Amako, Yutaka; Harold, Alexis; Toptan, Tuna; Chang, Yuan; Shuda, Masahiro (Frontiers in Microbiology, 2018)
Merkel cell polyomavirus (MCV) plays a causal role in 80% of Merkel cell carcinomas (MCC). MCV is clonally integrated into the MCC tumor genome which results in persistent expression of large T (LT) and small T (sT) antigen oncoproteins encoded by the early locus. In MCV-positive MCC tumors, LT is truncated by premature stop codons or deletions that lead to loss of the C-terminal origin binding (OBD) and helicase domains important for replication. The N-terminus Rb binding domain remains intact. MCV positive cell lines derived from MCC explants have been valuable tools to study the molecular mechanism of MCV-induced Merkel cell carcinogenesis. Although all cell lines have integrated MCV and express truncated LT antigens, the molecular sizes of the LT proteins differ between cell lines. The number of integrated viral genome copy also varies across cell lines, leading to significantly different levels of viral protein expression. Nevertheless, these cell lines share phenotypic similarities in cell morphology, growth characteristics, and neuroendocrine marker expression. Several low-passage MCV-positive MCC cell lines have been established since the identification of MCC. We describe a new MCV-positive MCC cell line, CVG-1 with features distinct from previously reported cell lines. CVG-1 tumor cells grow in more discohesive, loose round cell suspension and show dramatic size heterogeneity. It is the first cell line to encode an MCV sT polymorphism resulting in a unique leucine (L) to proline (P) substitution mutation at amino acid 144. CVG-1 possesses a LT truncation pattern identical to that of MKL-1 cells except for the last two C-terminal amino acids and also shows an LT protein expression level similar to MKL-1. Viral T antigen knockdown reveals that, like other MCV-positive MCC cell lines, CVG-1 requires T antigen expression for cell proliferation.